2012
DOI: 10.1186/1477-5956-10-63
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic bead-based salivary peptidome profiling for periodontal-orthodontic treatment

Abstract: BackgroundPatients with periodontitis seek periodontal-orthodontic treatment to address certain functional and aesthetic problems. However, little is known of the effect of periodontitis on orthodontic treatment. Thus, we compared the differences in peptide mass fingerprints of orthodontic patients with and without periodontitis by MALDI-TOF MS using a magnetic bead-based peptidome analysis of saliva samples. In this way, we aimed to identify and explore a panel of differentially-expressed specific peptides.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…1 H NMR proved useful to identify different metabolite signatures in children with and without caries [24]. As to MALDI-TOF profiling, it was combined to magnetic bead sample treatment and allowed to identify markers of periodontal disease in subjects with or without orthodontic treatment [25]. In all these studies, the patients were carefully selected based on homogenous clinical criteria, and gross medical confounding conditions were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR proved useful to identify different metabolite signatures in children with and without caries [24]. As to MALDI-TOF profiling, it was combined to magnetic bead sample treatment and allowed to identify markers of periodontal disease in subjects with or without orthodontic treatment [25]. In all these studies, the patients were carefully selected based on homogenous clinical criteria, and gross medical confounding conditions were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to SELDI-TOF MS profiling, magnetic RP beads and Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS have been used for salivary peptidome characterization under pathophysiological conditions, as, for example, in the evaluation of periodontal-orthodontic treatment (32). However, the information retrieved using these strategies is limited requiring complementary bottom-up approaches.…”
Section: Applications Of Advanced Omics Technologies: From Genes To Mmentioning
confidence: 99%
“…For instance, Zhang et al (32,44) used magnetic beads combined with MALDI-MS for saliva profiling in response to orthodontic procedures, solid foods, and teeth eruption, but only few MS peaks were significantly distinct among the conditions (27). While some quantitative methods developed for proteome studies were inherited, peptidome analysis has its own quantification traits.…”
Section: Applications Of Advanced Omics Technologies: From Genes To Mmentioning
confidence: 99%
“…In another study, the same authors found that peptide profiles of GCF from periodontal maintenance subjects could be used to predict sites with attachment loss [27]. Zhang et al compared the protein profiles of orthodontics patients with and without periodontitis using MALDI-TOF MS and found significantly different intensities of nine peaks, seven of which were higher in healthy subjects [28]. Chaiyarit et al analyzed salivary protein profiles in oral cancer, oral lichen planus, and chronic periodontitis and found that mass signals at 5,835.73 and 9,801.83 Da were significantly decreased in periodontitis patients compared to the two others oral diseases [29].…”
Section: Introductionmentioning
confidence: 99%